The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000486252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Different Drugs on Non-Motor Symptoms of Parkinson’s Disease: a Network Meta-Analysis

Abstract: Background/Aims: A network meta-analysis is used to compare the efficacy of ropinirole, rasagiline, rotigotine, entacapone, apomorphine, pramipexole, sumanirole, bromocriptine, piribedil and levodopa, with placebo as a control, for non-motor symptoms in Parkinson’s disease (PD). Methods: PubMed, Embase and the Cochrane Library were searched from their establishment dates up to January 2017 for randomized controlled trials (RCTs) investigating the efficacy of the above ten drugs on the non-motor symptoms of PD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Although traditional meta-analyses have been previously published, and network meta-analyses have compared drugs, little attention has been paid to the treatment of motor fluctuation that occurs in PD patients with a focus on comparing a limited group of classes or individual therapies (Stowe et al, 2011;Ren et al, 2014;Thorlund et al, 2014;Zhuo et al, 2017;Li et al, 2018;Mills et al, 2018;Zhao et al, 2019). In contrast to previous meta-analyses, the current analysis is the first network meta-analysis, and it integrates the broad basis of published evidence regarding randomized controlled trials to determine the efficacy and safety of drugs being used as adjuvant treatments with L-dopa for motor fluctuations in PD patients and allows a comprehensive evaluation of several categories of drugs under one overall analysis.…”
Section: Strengths and Comparisons With Other Studiesmentioning
confidence: 99%
“…Although traditional meta-analyses have been previously published, and network meta-analyses have compared drugs, little attention has been paid to the treatment of motor fluctuation that occurs in PD patients with a focus on comparing a limited group of classes or individual therapies (Stowe et al, 2011;Ren et al, 2014;Thorlund et al, 2014;Zhuo et al, 2017;Li et al, 2018;Mills et al, 2018;Zhao et al, 2019). In contrast to previous meta-analyses, the current analysis is the first network meta-analysis, and it integrates the broad basis of published evidence regarding randomized controlled trials to determine the efficacy and safety of drugs being used as adjuvant treatments with L-dopa for motor fluctuations in PD patients and allows a comprehensive evaluation of several categories of drugs under one overall analysis.…”
Section: Strengths and Comparisons With Other Studiesmentioning
confidence: 99%
“…Li et al conducted a network meta-analysis comparing ten drugs used in the treatment of non-motor symptoms of Parkinson's disease [6]. They included trials involving drugs from different drug classes (ropinirole, rasagiline, rotigotine, entacapone, apomorphine, pramipexole, sumarinole, bromocriptine, piribedil and levodopa).…”
Section: Introductionmentioning
confidence: 99%
“…They included trials involving drugs from different drug classes (ropinirole, rasagiline, rotigotine, entacapone, apomorphine, pramipexole, sumarinole, bromocriptine, piribedil and levodopa). They found that among the drugs included in their analysis, apomorphine appeared to be the most efficacious [6].…”
Section: Introductionmentioning
confidence: 99%
“…All sessions were capped at 90 min to help ensure that each of the DA drugs would be active for the duration of the experiment. Dihydrexidine has been shown to have a relatively short half‐life of 1–2 hr (Taylor et al., ; Blanchet et al., ; For review also see: Mailman, Huang, & Nichols, ; Salmi, Isacson, & Kull, ), while sumanirole has been shown to be effective for 3–8 hr depending on the species and delivery method (Barone, Lamb, Ellis, & Clarke, ; Li et al., ; McCall et al., ).…”
Section: Methodsmentioning
confidence: 99%